2012
DOI: 10.1136/ejhpharm-2012-000074.168
|View full text |Cite
|
Sign up to set email alerts
|

The performance improvements of the 3rd generation robot for the automated compounding of oncology drugs

Abstract: Background The collaboration established in 2007 between the Oncology Pharmacy of the University Hospital of Ancona and the Loccioni Group was aimed at implementing, validating and integrating the robotised system for the chemotherapic drugs compounding in the day-to-day pharmacy activity. Currently the Oncology Pharmacy is almost totally automated (95%) and Loccioni has its clinical site for the continuous engineering. During this 4-year period, the constant implementation gave rise to three generations of ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Station ® (Omnicell) were not selected because the versions reported are no longer marketed in Europe. As previously reported by Batson et al, 13 Apoteca Chemo ® was the most comprehensively studied robot with 13 publications 3,[18][19][20][21][22][23][24][25][26][27][28][29] (5 additional publications since 2017). For four robots (Intelligent Compounding System ICS ® , Riva ® , Equashield Pro ® and Pharmoduct ® ), no publications were available.…”
Section: Review Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Station ® (Omnicell) were not selected because the versions reported are no longer marketed in Europe. As previously reported by Batson et al, 13 Apoteca Chemo ® was the most comprehensively studied robot with 13 publications 3,[18][19][20][21][22][23][24][25][26][27][28][29] (5 additional publications since 2017). For four robots (Intelligent Compounding System ICS ® , Riva ® , Equashield Pro ® and Pharmoduct ® ), no publications were available.…”
Section: Review Resultsmentioning
confidence: 99%
“…Robots may differ in the types of compatible drug vials due to their size or their collar size (Table 3). With the Apoteca Chemo ® robot, Iwamoto et al 19 and Palma and Bufarini 23,24 reported using 56 and 160 different vials of 34 and 56 anticancer drugs, respectively. In the robots of the present study, a new drug could be added without the intervention of the manufacturer in the hospital.…”
Section: Type Of Anticancer Preparations Producedmentioning
confidence: 99%